Treatment response and outcome of children with T-cell acute lymphoblastic leukemia expressing the gamma-delta T-cell receptor - Ching-Hon Pui; Deqing Pei; Cheng Cheng; Suzanne L. Tomchuck; Scarlett N. Evans; Hiroto Inaba; Sima Jeha; Susana C. Raimondi; John K. Choi; Paul G. Thomas; Mari Hashitate Dallas (OncoImmunology, 2019)
T-cell malignancies expressing the γδ T-cell receptor (TCR) are often associated with poor prognosis. Here, we determined the clinical outcome of pediatric patients with T-cell acute lymphoblastic leukemia (T-ALL) expressing the γδ TCR. Of 100 newly diagnosed T-ALL patients, 93 had γδ TCR analysis performed at diagnosis. Repertoire was evaluated by paired sequencing of the rearranged TCR. All patients received intensified chemotherapy and those with minimal residual disease (MRD) ≥ 1% on day 42–46 became candidates for hematopoietic cell transplantation. Of the 93 T-ALL patients, 12 (13%) had γδ T-ALL and 11 (12%) had early T-cell precursor (ETP) ALL. Compared to the remaining 70 T-ALL patients, the γδ T-ALL patients were more likely to have MRD ≥ 1% on day 15–19 (67% vs. 33%, P = 0.03) and day 42–49 (33% vs. 7%; P = 0.007) of remission induction. The 10-year overall survival for γδ T-ALL patients (66.7% ± 22.2%) were lower than that of T-ALL patients (93.3% ± 7.3%, P = 0.001). TCR analysis demonstrated a conserved clonotype. In conclusion, the data suggest that children with γδ T-ALL may have a poor response to remission induction, based on MRD levels and decreased survival than the other T-ALL patients, despite receiving risk-directed therapy.